PERAN MEDIASI NILAI PENJUALAN UNIK PADA PENGARUH MANAJEMEN STRATEGI DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN ONLINE - Wirawan, Soni; Syahputra, Hendra; Minullah, Minullah (Relawan Jurnal Indonesia, 2025)
This study aims to evaluate strategies in the recruitment and selection process of interns as part of companies' efforts to build sustainable talent development pipelines, using a desk-based approach. Information was collected through a review of relevant academic journals, scientific articles, and research reports. The study results indicate that successful recruitment strategies include utilizing social media platforms, strengthening the company's image as an attractive employer, and collaborating with higher education institutions. Furthermore, a systematic intern selection process—through interviews, aptitude tests, and the use of technology such as an Applicant Tracking System (ATS)—has been shown to improve accuracy in selecting suitable candidates and reduce potential bias. Several supporting factors identified include management involvement, the use of digital technology, and partnerships with educational institutions, while key barriers include limited resources and intern readiness. Overall, the implementation of a well-planned internship program not only improves the effectiveness of the recruitment process but also strengthens workforce loyalty and sustainability within the company. These findings provide theoretical contributions to human resource management studies and offer practical recommendations for organizations in optimally managing talent development